KEHIDUPAN SISIAL EKONOMI BURUH PABRIK KELAPA SAWIT PTP. NUSANTARA VI OPHIR KECAMATAN LUHAK NAN DUO KABUPATEN PASAMAN BARAT (2005-2012) - ARISTIANI, FITRI - (Pendidikan Sejarah, 2014)
The problem in this case is about worker life where they and other have different category and give effect toward life and need life. Social-economic worker grade relate with work facility worker produce manufacturing swit coconut, high and low income of worker is depend on category and absent in work.Primary case is discussed in this research is about social-economic life of factory worker at PTP. Nusantara VI Ophir Kecamatan Luhak Nan Duo Kabuoaten Pasaman Barat. The kinds of the research is history research with qualitative method where research method is include four steps such as: Heuristic, Source Critique, intepretation and Historiography with follow some benefit of sources that are Primary and secondary sources which are got from libray study, safe, company document, interview and direct observation to research location.Based the result of research can be concluded that develop of factory worker at PTP. Nusantara Ophir VI from year 2005 that amount little worker if it compare with year 2012 which start improving amount worker at PTP. Nusantara VI Ophir do high and low condition where is depend on producing sawit coconut every mount and can give effect toward income of worker. Meanwhile, income is picture about economic posotion and does not go from work facility in company which develop life worker.